Regionalism, Federalism and Internationalism in First World War France - Bouchard, Carl (Pluralism and the Idea of the Republic in France, 2012)
The Société Proudhon was founded in 1917, in the midst of the most difficult year of the First World War. Its first director was Jean Hennessy (1874–1944), deputy from the Charente and member of the famous dynasty of cognac producers. The letter that announced its creation was distributed in political and intellectual circles, and insisted that the society aimed ‘to help the formation of a Society of Allied states, presently struggling against the militarist empires. It will set up the federation of democracies against the conspiracy of imperialists’.1 There was nothing particularly original in the tone or spirit of the letter. A number of societies and individuals were calling for an alliance of democracies to defeat the German autocracy, and an international organisation equipped with military power to punish aggressor states, if not a world parliament for the establishment of everlasting peace. The First World War was effectively the moment of a remarkable individual and collective craze, seeking new methods for a lasting peace after the end of the war.2
Keywords: Intellectual Circle; Lasting Peace; Peace Movement; Regionalist Debate; Regionalist Movement